Syntheses of [C]2- and [C]3-trifluoromethyl-4-aminopyridine: potential PET radioligands for demyelinating diseases - Ramos-Torres, Karla M; Zhou, Yu-Peng; Yang, Bo Yeun; Guehl, Nicolas J; Sung-Hyun, Moon; Telu, Sanjay; Normandin, Marc D; Pike, Victor W; Brugarolas, Pedro (MedChemComm, 2020)
Trifluoromethyl groups are of great interest in PET radiopharmaceuticals. Radiolabelled 4-aminopyridine (4AP) derivatives have been proposed for imaging demyelinating diseases. Here, we describe methods for producing 11 C-trifluoromethylated derivatives of 4AP and present early imaging results with [ 11 C]3-trifluoromethyl-4AP in a rhesus macaque. This study shows the utility of [ 11 C]CuCF 3 for labelling pyridines and provides initial evidence for the potential use of [ 11 C]3-trifluoromethyl-4AP as a PET radioligand. [ 11 C]fluoroform was used to produce 11 C-trifluoromethylated derivatives of 4-aminopyridine with high molar activity for PET imaging of the brain.